Pengaruh Online Customer Review, Influencer Marketing, Dan Kualitas Website Terhadap Keputusan Pembelian Online Shop Shopee Siswa SMK Negeri 1 Karanganyar - Hessa Fadhela Putri; Cicilia Dyah; Tutik Susilowati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to find out whether online customer reviews influence online shop shopee purchasing decisions for students of SMK Negeri 1 Karanganyar, influencer marketing on online shop shopee purchasing decisions for students of SMK Negeri 1 Karanganyar, and website quality on online shop shopee purchasing decisions for students of SMK Negeri 1 Karanganyar. ; and to find out whether online customer reviews, influencer marketing, and website quality jointly influence the purchasing decisions of students at SMK Negeri 1 Karanganyar. This research uses quantitative techniques with correlational methods. The sample for this research was OTKP and MPLB students in classes X, XI and XII who had shopped via the Shopee application, totaling 140 students. The results of this research show that: 1) online customer reviews have a positive and significant influence on purchasing decisions as evidenced by the calculated t value (7.935) > t table (1.977) and a significance value of 0.000 < 0.05. 2) influencer marketing has a positive and significant influence on purchasing decisions as evidenced by the calculated t value (2.206) > t table (1.977) and a significance value of 0.009 < 0.05. 3) website quality has a positive and significant effect on purchasing decisions as evidenced by the calculated t value (4.097) > t table (1.977) and a significance value of 0.001 < 0.05. 4) there is a positive and significant influence between online customer reviews, influencer marketing, and website quality on purchasing decisions as evidenced by the value of Fcount (95.480) > Ftable (2.67) and a significance value of 0.000 < 0.05.